IMPEMENTASI STRATEGI PEMBELAJARAN PENINGKATAN KEMAMPUAN BERPIKIR DALAM MENINGKATKAN HASIL BELAJAR EKONOMI DI SMA N 1 LIRIK - Rejeki, Sri; Suarman, Suarman; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the low learning outcomes of students inparticipating in economics learning. The purpose of this reasearch is to find out.Implementation of learning strategies to improve thinking skills in increasing economiclearning outcomes at SMA N 1 Lirik. The population in this study were all students ofclass X SMA N 1 Lirik which consisted of 6 classes. The sample selection was carriedout by using a clutser sampling technique so that the class X IIS 1 sample was producedwith 25 students. The data collection techniques were observation using researchinstruments, observation sheet, teacher activity and student, and test technique usingpretest and posttest research instruments. Futhermore, the data were analyzed using thet test, and the normalized gain test with the help of SPSS version 22. When viewed fromthe results of statistical test analysis with the t test data, posttest value of theexperimental and control classes, then the sig value of the experimental and controlclasses, then the sig value is 0.000<0.05 and it can be said that there is significantdifference between pretest and posttest. And when viewed from the normalized gain test,the increase in the pretest and posttest scores obtained an n-gain value of 0,57 in themoderate category, it can be concluded that the learning strategy for increasingthinking skills ( SPPKB ) in class X can improve learning outcomes in economicssubjects.Key Words: Learning Strategies , SPPKB, Learning Outcomes.